2019
DOI: 10.1002/lary.27940
|View full text |Cite
|
Sign up to set email alerts
|

Does paranasal sinus development affect olfactory fossa depth and lateral lamella length?

Abstract: Objectives: To investigate the olfactory fossa depths and lateral lamella lengths of patients with different types of developmental disorders of paranasal sinuses in comparison with normal controls.Study Design: Retrospective, archival, radio-anatomical study. Methods: We included 58 patients with maxillary sinus hypoplasia, 50 patients with frontal sinus hypoplasia/aplasia, 50 patients with sphenoid sinus hypoplasia/aplasia, and 40 normal controls. Reviewing paranasal computerized tomography scans, we noted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…1,2) Çomoğlu, et al 1) reported deeper olfactory fossa in extensively pneumatized FS cases, with a mean LLL of 4.17±1.44 mm in FS type I, 5.15± 1.50 mm in type II, and 5.60±1.41 mm in type III. Kayabasi, et al 3) and two other studies 1,2) surveyed the Turkish people and obtained different results.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…1,2) Çomoğlu, et al 1) reported deeper olfactory fossa in extensively pneumatized FS cases, with a mean LLL of 4.17±1.44 mm in FS type I, 5.15± 1.50 mm in type II, and 5.60±1.41 mm in type III. Kayabasi, et al 3) and two other studies 1,2) surveyed the Turkish people and obtained different results.…”
Section: Discussionmentioning
confidence: 95%
“…In our study, the mean LLL of type II and III were significantly greater than that of type I but the MS and SS types and the LLL were not significantly correlated. Kayabasi, et al 3) observed that the pneumatization defects of MS, FS, and SS were related to deeper olfactory fossa and longer lateral lamella. In their study, the mean LLL of the FS aplasia group was 6.53±1.78 mm, 5.98±1.94 mm in the FS hypoplasia group, and 4.28±1.52 mm in the control FS group (p<0.001).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations